WEIGHTED STATISTICAL CONVERGENCE - Karakaya, V.; Chishti, T. A. (SPRINGER INTERNATIONAL PUBLISHING AG, 2009)
In this paper, the notion of ((N) over bar, p(n))- summability to generalize the concept of statistical convergence is used. We call this new method weighted statistically convergence. We also establish its relationship with statistical convergence, (C,1)-summability and strong ((N) over bar, p(n)) -summability.
Keywords: Norlund-type means; weighted statistical convergence; sequence spaces; Cesaro summability; TAUBERIAN CONDITIONS; SUMMABILITY; RESPECT; MODULUS; FOLLOWS; Science & Technology - Other Topics